The human footprint a global environmental history - Penna, Anthony N. (Wiley Blackwell, 2015)
Updated to reflect the most recent research, the second edition of The Human Footprint expands upon Anthony N. Penna's multidisciplinary global history of Earth from its beginnings to the present day. While initial chapters focus on "bighistory," placing human history within a cosmic framework, succeeding chapters reveal the great natural and human transformations that have shaped civilization over millennia. Using the most up-to-date research from geologists, anthropologists, archaeologists,economists, historians, and others, individual chapters expand upon single topics within broader themes relating to Earth's history and human origins; mass migrations and the rise of agriculture; nutrition and population growth and the rise of cities, manufacturing, and industry; world trade, mass consumption, and new world ecology; modes of energy use, and more. New research into the world's warming climate serves to reinforce the fragile nature-of world-human history interdependencies. Timely and essential, The Human Footprint provides illuminating insights into the future of our planet by revealing the interconnectedness of humans and nature throughout our past. Book jacket